ANALISIS SCP (STRUCTURE, CONDUCT, PERFORMANCE) KOMODITI SAGU DIKECAMATAN TEBING TINGGI TIMUR KABUPATEN KEPULAUAN MERANTI (STUDI KASUS DI DESA SUNGAI TOHOR) - Elfis Merdani; Ermi Tety; Deby Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This research purpose to analyze the structure, behavior, and appearance of sago commodity in Sungai Tohor village, Tebing Tinggi Timur regency. Research conducted using the method of the survey. Respondents made up of farmers and the entire marketing agencies involved in commodity Commerce of Sago. Determination of the samples of farmers using simple random sampling method, while for merchants using the method of census. The data analysis done in a descriptive and quantitative. The structure of the market are identified through amount of market participants, the obstacles out of market entry, the concentration ratio, market share and the herfindahl index. The behavior of the market is seen through the practice of the establishment of price, correlation of price and price transmission. The appearance of the market observed from the margins of marketing. Market structure including the oligopsony, seen from the amount the seller more than a buyer, and the existence of barriers to market in or out. The value of the present market share traders gatherers ranged from 0.09-0.12, while the present major traders of 1. Herfindahl index value present merchant gatherers of 0.01. While in major merchant level of 1. Analysis of market behavior suggests that the end consumer (merchants) is the dominant part in the determination of price. The commodity price levels in sago farmers correlated strongly with the price at the level of the final consumer. Price transmission elasticity value is < 1. Average marketing margin commodities sago is Rp 1,057,-/kg. Types of commodity markets sago in the village of Sungai Tohor is oligopsony. The average marketing costs at the level of traders collecting is Rp. 647,-/kg, with an average profit rate was Rp. 410,-/Kg. Keywords : Sago, Structure, Behavior, Appearance, Market